Lung carcinosarcoma - Campos Pierri, Néstor; Revetria, Ricardo; Veroli, Antonio; Mascari, José L.; Andrade, Eduardo; Pizarossa, Carlos; Chiribao, Concepción (Cirugía del Uruguay, 1986)
Presentlng the flrst case of lung carclnosarcoma descrlbed in Uruguay. Descrlptlon of the case correspondlng to an abscessed tumor treated by lobectomy. Patient survlvlng some months. Author dlscusses the case and provides blbliographlc reference.